Open market operations - Meek, Paul; Federal Reserve Bank of New York (New York : Federal Reserve Bank of new York, 1969)
The book examines the monetary and fiscal measures taken in the 1960s to achieve the nation's economic objectives.
osc 8/2/17
Loans
Keywords: Monetary policy; Open Market Operations